Evaluation of Techniques for the Presentation of Laboratory Data. I: Time Needed for Interpretation - Verheij, R.; Hoeke, J. O. O.; Bonke, B.; van Strik, R.; Gelsema, E. S. (Methods of Information in Medicine, 1997)
Four tabular and two graphical techniques for the presentation of laboratory test results were evaluated in a reaction-time experiment with 25 volunteers. Artificial variables and values were used to represent sets of 12 laboratory tests to eliminate the possible effects of clinical experience. Analyses focused on reaction times for correctly classified sets of data. For comparable data sets, Presentation Techniques (PT) that use color, always allow faster interpretation than PTs that do not use color, or use only a simple marker. Color-coded tables yielded an improvement in median reaction time of approximately six times or better, as compared to the reference PT (a tabular PT without any hints). For the color-coded graphs, the improvement rate was approximately 2.5 or better.
Keywords: Clinical Laboratory; Graphical Display; Data Presentation; Data Interpretation; Evaluation